Prostate Cancer in XX and first decade of XXI centures - O. M. Sidorenko; O. P. Kolesnik; S. V. Merzlyak (Zaporozhye State Medical University, 2012)
Prostate cancer is the one of the most common malignancy in men in developed countries. Annually, 782,647 new cases of prostate cancer recorded in the world at least. The highest incidence rates are typical for North America, Australia and Western Europe, the lowest - in Asia, China and North Africa. Ukraine has also noticed a clear tendency to increase the incidence of cancer prostate. In recent years the death rate from prostate cancer in the world decreased through improved awareness, improving early diagnosis and treatment.